The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1415-47572008000400005
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation analysis of the tumor suppressor gene CDKN2B in Brazilian leukemia patients

Abstract: The aim of this work was to evaluate the methylation profile of the p15 (CDKN2B) gene in Brazilian patients with leukemia and to correlate the CDKN2B gene expression with the percentage of methylated CpG dinucleotides in its promoter region. Thirty-one samples from six patients with acute lymphocytic leukemia (ALL), four with chronic myeloid leukemia (CML), and 21 with acute myeloid leukemia (AML) were evaluated by MSP (Methylation-Specific PCR). The CDKN2B gene was found to be methylated in four (67%) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…In MDS BM-CD33 cells these mechanisms involve the Cyclin D2, CDK4 and CDK6 proteins, whereas in AML cells the mechanisms are dependent on p15. This hypothesis is supported by published data showing p15 is one of the genes most frequently inactivated in leukaemic patients by DNA methylation and that p15 methylation in AML patients is associated with poor prognosis [40], [41].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In MDS BM-CD33 cells these mechanisms involve the Cyclin D2, CDK4 and CDK6 proteins, whereas in AML cells the mechanisms are dependent on p15. This hypothesis is supported by published data showing p15 is one of the genes most frequently inactivated in leukaemic patients by DNA methylation and that p15 methylation in AML patients is associated with poor prognosis [40], [41].…”
Section: Discussionsupporting
confidence: 54%
“…In THP1 the effect of vorinostat on the expression of most of these genes was less pronounced than in K562 and HL60. Interestingly, some genes, such as p15 (Figure 4A, 1), and Cyclin D1 (Figure 4A, 2), often deregulated in MDS and AML and associated with worse prognosis [7], [40], [41], [42], were modulated to a greater extent in HL60, whereas AXL (Figure 4A, 1), frequently up-regulated in AML and associated with adverse prognosis [30], was more marked in K562.…”
Section: Resultsmentioning
confidence: 99%
“…Another study demonstrated that folic acid prevents NTDs by partially reducing or reversing aberrant DNA methylation via the one‐carbon metabolic pathway (Blom et al, 2006). The DNA methylation state is maintained primarily by DNMTs, which catalyze the transfer of a methyl group from the methyl precursor, SAM, onto the 5‐position of certain cytosines in CpG dinucleotides (Lima et al, 2008). DNA methylation is an epigenetic event that plays an important role in regulating gene function.…”
Section: Discussionmentioning
confidence: 99%
“…It encodes both the ARF protein, which binds the p53-stabilizing protein MDM2, and the INK4 protein, a cyclin-dependent kinase inhibitor. Loss-of-function mutations in CDKN2A are responsible for familiar forms of human melanoma (LIMA et al 2008;HELL-STRÖM et al 2010).…”
mentioning
confidence: 99%